Co-creation for Responsible Research and Innovation: Experimenting with Design Methods and Tools - Deserti, Alessandro; Real, Marion; Schmittinger, Felicitas (Springer Series in Design and Innovation, 2022)
This open access book summarizes research being pursued within the SISCODE (Society in Innovation and Science through CO-DEsign) project, funded by the EU under the H2020 programme, the goal of which is to set up an analytical, reflective and learning framework to explore the transformations in initiatives and policies emerging from the interaction between citizens and stakeholders. The book provides a critical analysis of the co-design processes activated in 10 co-creation labs addressing societal challenges across Europe. Each lab as a case study of real-life experimentation is described through its journey, starting from the purpose on the ground of the experimentation and the challenge addressed. Specific attention is then drawn on the role of policies and policy maker engagement. Finally, the experimentation is enquired in terms of its output, transformations triggered within the organization and the overall ecosystem, and its outcomes, opening the reasoning towards the lessons learnt and reflections that the entire co-creation journey brought.
Keywords: Co-création; Innovation; Libre accès; Outils; Recherche; Étude de cas

A dual-functional social innovation process model for low-cost houses through university-enabled initiative - Belayutham, Sheila; Ibrahim, Che Khairil Izam Che; Zulkifli, Assrul Reedza; Ibrahim, Norhati (Construction Innovation-England, 2019)
The purpose of this study is to develop a dual-functional university-enabled social innovation process model on the subject of low-cost houses that addresses the distinct elements of social obligation and university teaching-learning. Design/methodology/approach This study has predominantly adopted a longitudinal single case study approach, where data have been collected through interviews, survey, participant observation, direct observation and document review. The case study details on the social innovation processes, which was conducted by Universiti Teknologi MARA, Malaysia. Findings This study has demonstrated the social innovation processes toward addressing the issue of insufficient low-cost houses, concurrently benefitting the teaching-learning dimension. Three sub-innovations have been highlighted in the developed social innovation process model, which are collaboration process, teaching-learning and design-construct innovation. Originality/value The development of the social innovation process model for low-cost houses through university-enabled initiative is a novel establishment, particularly for developing nations, as limited studies have been conducted in this regard. The significant insights into how university could play a role in addressing major social issues, along with their core focus (teaching-learning and research development), is a breakthrough for further diffusions of social innovation by universities.
Keywords: Asie; Enseignement; Innovation sociale; Recherche; Rôle des universités; logement

Living Labs, innovation collaborative et écosystèmes : le cas de l’initiative « Concept Maturity Levels » dans les Medtech - Béjean, Mathias; Picard, Robert; Bréda, Gabrièle (Innovations, 2021)
Les Living Labs (LLs) sont de nouvelles formes de laboratoires mettant en œuvre des approches collaboratives et expérimentales centrées sur les utilisateurs. Récemment, les capacités des LLs à développer des réseaux d’innovation ouverts et collaboratifs ont été soulignées. Mais les recherches sont encore peu nombreuses, alors même que le phénomène ne cesse d’évoluer en pratique. En s’appuyant sur l’analyse longitudinale d’une initiative en cours, les « Concept Maturity Levels Santé », impulsée par le Forum des Living Labs en Santé et Autonomie, cet article présente une recherche abductive visant à explorer et caractériser la manière dont les LLs peuvent contribuer, au-delà de projets d’innovation temporaires, à structurer des écosystèmes d’innovation ouverts et collaboratifs sur le long terme. En sus de contribuer à la littérature sur les LLs, l’article ouvre de nouvelles pistes de caractérisation des écosystèmes communautaires d’innovation jusqu’ici encore peu étudiés.Code JEL : M100
Keywords: France; Innovation collaborative; Laboratoire vivant; Recherche; Réservé UdeM; Santé

Expérimenter la recherche-projet en doctorat : applications dans les champs de la santé et du handicap - Fournier, Pierre; Ménard, Manon; Wrembel, Élisa (Etudes de communication, 2021)
Nous proposons un regard réflexif sur deux expériences de recherche-projet menées dans le cadre de thèses de doctorat. Notre réflexion porte sur les apports et limites de cette démarche dans le cadre de projets ancrés dans les champs de la santé et du handicap, plus spécifiquement des troubles du sommeil et des troubles du spectre de l’autisme. La proposition repose sur la démonstration de l’intérêt de la conception participative propre à la recherche-projet dans ces domaines sensibles au sein desquels l’enjeu de l’inclusion des acteurs apparaît comme majeur.
Keywords: Innovation inclusive; Innovation sociale; Projets participatifs; Recherche; Réservé UdeM

Rediscovering the Cooperative Enterprise: A Systematic Review of Current Topics and Avenues for Future Research - Camargo Benavides, Andres Felipe; Ehrenhard, Michel (VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations, 2021)
For decades, the cooperative enterprise (CE) produces market goods and/or provides services in the interest to its members, such as communities, customers, and suppliers. The upsurge of interest in social enterprises, and their balancing of social and economic interests, has also led to a renewed interest in CEs, often seen as a speciﬁc type of social enterprise. However, from an organizational perspective, this renewed interest has been both limited and scattered over a variety of ﬁelds. In this paper, we systematically review papers on CE in the mainstream organizational literature, deﬁned as literature in the ﬁelds of economics, business, management and sociology. Our review integrates and synthesizes the current topics in the mainstream organizational literature and provides a number of avenues for future research. In addition, we compare our ﬁndings in the organizational literature to the social issues literature as these appeared to be quite complimentary. We found multilevel studies, determination of social impact—in particular measurable impact, managerial practices for sustainable (organisational) development, and the entrepreneurial opportunity generation process as the four key avenues for future research.
Keywords: Coopératives; Entreprise; Entreprise sociale; Recherche; Réservé UdeM

Nourishing the Social Innovation Debate with the “Social Technology” South American Research Tradition - Marlei, Pozzebon; Tello-Rozas, Sonia; Heck, Isabel (Voluntas, 2021)
Inspired by the South American research tradition known as “social technology,” this article proposes an operational framework to advance the understanding of mechanisms that help to promote social transformation. To illustrate its theorizing potential, we apply the framework to a nonprofit organization–Parole d’excluEs–that was created in Montreal (Canada) in 2006 and that has been promoting citizen mobilization and commitment to social change (parole-dexclues.ca). To that end, we offer a theoretical paper with an empirical illustration as a first step in a reflection on employing a global South theoretical lens–drawing on the concept of social technology–to make sense of a global North social innovation experience and to advance existing knowledge on the mechanisms of social transformation. The results contribute to social innovation research and practice, particularly at the interface between the management and nonprofit literatures.
Keywords: Amérique latine; Canada; Changement social; Innovation sociale; Montréal; Recherche; Technologie sociale; Transformations

Technological interventions in social business: Mapping current research and establishing future research agenda - Soni, Gunjan; Mangla, Sachin Kumar; Singh, Pallavi; Dey, Bidit L.; Dora, Manoj (Technological Forecasting and Social Change, 2021)
Social businesses, despite having a huge potential to generate substantial and sustainable value, are often structurally and financially fragile. Technological interventions, such as social media analytics, big data, Internet of Things, and blockchain can help social businesses by leveraging the practices towards financial and operational sustainability. This study is the first of its kind in that it analyses existing scholarly works on social businesses using bibliometric analysis. In so doing, this paper presents an in-depth statistical analysis of the literature on technological interventions in sustainable social business, showcasing the development of the scholarship, major themes, and possible future research trajectories. The SCOPUS database is used to identify a large section of articles. The study shows that most of the work in social business has been done by scholars based in developed countries, with limited contributions emanating from developing countries. The study proposes a framework for the use of technology in sustainable social businesses with focus areas of research such as social innovation, digital technology, information systems, and decision making for sustainability. The results show that digital technologies are increasingly being accepted as tools for the sustainability and scalability of social businesses. The paper offers useful recommendations for future research in relevant fields.
Keywords: Entreprise sociale; Recherche; Réservé UdeM; Social business model; Statistiques; Technologie; numérique

Social Science and Intelligence Design - Mulgan, Geoff (Social Innovation: How Societies Find the Power to Change, 2019)
In this chapter I turn to how social science can be adapted to the challenges and tools of the 2020s, becoming more data driven, more experimental and fuelled by more dynamic feedback between theory and practice. Social science at its grandest is the way societies understand themselves: why they cohere or fall apart; why some grow and others shrink; why some care and others hate; how big structural forces explain the apparently special facts of our own biographies. It observes but also shapes action, and then learns from those actions.Starting with the idea of social science as collective selfknowledge, I describe how new approaches to intelligence of all kinds can help to reinvigorate it. I begin with data and computational social science and then move on to cover the idea of social R&D and experimentation, new ways for universities to link into practice, including social science parks, accelerators tied to social goals, challenge-based methods and social labs of all kinds, before concluding with the core argument: an account of how social science can engage with the emerging field of intelligence design. This is, I hope, a plausible and desirable direction of travel.The rise of data-driven and computational social ScienceWe are all familiar with the extraordinary explosion of new ways to observe social phenomena, which are bound to change how we ask social questions and how we answer them. Each of us leaves a data trail of whom we talk to, what we eat and where we go. It's easier than ever to survey people, to spot patterns, to scrape the web, to pick up data from sensors or to interpret moods from facial expressions. It's easier than ever to gather perceptions and emotions as well as material facts – for example, through sentiment analysis of public debates. And it's easier than ever for organisations to practise social science – whether it's investment organisations analysing market patterns, human resources departments using behavioural science or local authorities using ethnography.These tools are not monopolised by professional social scientists. In cities, for example, offices of data analytics link multiple data sets and governments use data to feed tools using AI – like Predpol or HART – to predict who is most likely to go to hospital or end up in prison.
Keywords: Changement social; Recherche; Réservé UdeM; Université

Sustainability-Oriented Social Innovation Design: The Value of Co-Creation - Yan, Wu; Lei, Ren; Keye, Li (2019 IEEE Eurasia Conference on Biomedical Engineering, Healthcare and Sustainability (ECBIOS), 2019)
From the perspective of sustainability, this paper analyzes how stakeholders realize sustainable social innovation through co-creation. Through literature and case analysis, based on the group classification of social networks, this paper proposes three elements of social innovation: place creation, situation creation and relationship structure, and further sorts out the co-creation of meaning co-creation, behavior co-creation and value co-creation. The research shows that co-creation is a practical activity based on cultural identity, group interaction and resource integration, and stakeholders can achieve the goal of sustainable social innovation through meaning co-creation, behavior co-creation and value co-creation.
Keywords: Co-création; Communautaire; Coopération; Durabilité; Développement durable; Innovation sociale; Innovation sociale durable; Nouvelles technologies; Recherche; Réservé UdeM

Unpacking the role of universities in the emergence, development and impact of social innovations – A systematic review of the literature - Bayuo, Blaise Booponoyeng; Chaminade, Cristina; Göransson, Bo (Technological Forecasting and Social Change, 2020)
Widening income and knowledge inequalities have led to growing expectations for universities to integrate social innovation in their core missions as a response to societal problems. This systematic review of literature provides an overview of the state-of-the-art of knowledge on the role of the university in enabling social innovation through its missions of teaching, research and third mission. It also identifies knowledge gaps in the field. A bibliometric approach wasused to identify and analyze books, journal articles and reports examining factors driving social innovation activities at universities, organizational and insitutional change to accommodate such activities as well as their impact. The review reveals that the literature on university engagement in socially-oriented activities as part of the third mission of the university is conceptually well developed and a growing field of inquiry. It also points to gaps in the knowledge base; relatively few studies address issues related to institutional change and incentive structures that influences the ability of universities to engage in social innovation. Likewise, impact studies on social innovation activities at universities are scarce. Further research that builds an impact measurement framework would support the process of integrating social innovation activities in the three missions of the university.
Keywords: Innovation sociale; Mesure d'impact; Recherche; Réservé UdeM; Rôle des universités; Université

Strategic Corporate Social Responsibility (SCSR): a systematic literature review - Athanasiadou, Chrisalena; Chatzoudes, Dimitrios; Theriou, Georgios (2020 Fourth World Conference on Smart Trends in Systems, Security and Sustainability (WorldS4), 2020)
Over the past few decades, Corporate Social Responsibility (CSR) has been perceived as an antecedent of competitive advantage. It was, moreover, placed at the top of the business agenda and recognized as a key driver of performance. Under this context, the present study sets to investigate how strategic CSR (SCSR) affects organizational performance and whether firms operating in “controversial” sectors should adopt SCSR activities. To this aim, this study reviews the body of knowledge on the topic, through a systematic review of the literature. After searching for academic publications in the Scopus database and selecting publications based on their relevance, 32 studies have been included in the review. Their analysis sheds light on common findings and contradicting arguments. Results show the main attributes of strategic, as opposed to non-strategic CSR activities. The importance of effective communication of SCSR activities is highlighted. SCSR is linked to “shared value”, as well as to competitive advantage, social innovation and good reputation. Voices of criticism focus on using SCSR as an empty promise that is used to counteract unethical behavior. Finally, more research is needed on the implementation of SCSR activities during recessionary periods.
Keywords: Co-création; Data collection; Innovation; Libre accès; Méthodes; Recherche; Relations industrielles

La recherche partenariale au Québec : tendances et tensions au sein de l’université - Dumais, Lucie (2011)
L’article tente dans une première partie de produire un classement des pratiques de recherche partenariale ayant cours dans les universités au Québec. Sans être une investigation systématique, elle puise dans diverses disciplines des sciences sociales et dans divers domaines de recherche. Deux tendances semblent se dessiner, l’une plus proche de la vision émancipatrice et l’autre plus axée sur les stratégies d’innovation sociale. La réflexion se poursuit par l’exposition, en seconde partie d’article, de trois nouveaux enjeux engendrés par l’essor de la recherche partenariale au sein de l’institution universitaire : la tension avec la recherche traditionnelle, la démarcation du savoir universitaire des autres types de savoirs et, enfin, l’éthique de la recherche.
Keywords: Partenariat; Québec; Recherche; Université

Strategic Corporate Social Responsibility (SCSR): a systematic literature review - Athanasiadou, Chrisalena; Chatzoudes, Dimitrios; Theriou, Georgios (2020 Fourth World Conference on Smart Trends in Systems, Security and Sustainability (WorldS4), 2020)
Over the past few decades, Corporate Social Responsibility (CSR) has been perceived as an antecedent of competitive advantage. It was, moreover, placed at the top of the business agenda and recognized as a key driver of performance. Under this context, the present study sets to investigate how strategic CSR (SCSR) affects organizational performance and whether firms operating in “controversial” sectors should adopt SCSR activities. To this aim, this study reviews the body of knowledge on the topic, through a systematic review of the literature. After searching for academic publications in the Scopus database and selecting publications based on their relevance, 32 studies have been included in the review. Their analysis sheds light on common findings and contradicting arguments. Results show the main attributes of strategic, as opposed to non-strategic CSR activities. The importance of effective communication of SCSR activities is highlighted. SCSR is linked to “shared value”, as well as to competitive advantage, social innovation and good reputation. Voices of criticism focus on using SCSR as an empty promise that is used to counteract unethical behavior. Finally, more research is needed on the implementation of SCSR activities during recessionary periods.
Keywords: Co-création; Data collection; Innovation; Libre accès; Méthodes; Recherche; Relations industrielles

Social Science and Intelligence Design - Mulgan, Geoff (Social Innovation: How Societies Find the Power to Change, 2019)
In this chapter I turn to how social science can be adapted to the challenges and tools of the 2020s, becoming more data driven, more experimental and fuelled by more dynamic feedback between theory and practice. Social science at its grandest is the way societies understand themselves: why they cohere or fall apart; why some grow and others shrink; why some care and others hate; how big structural forces explain the apparently special facts of our own biographies. It observes but also shapes action, and then learns from those actions.Starting with the idea of social science as collective selfknowledge, I describe how new approaches to intelligence of all kinds can help to reinvigorate it. I begin with data and computational social science and then move on to cover the idea of social R&D and experimentation, new ways for universities to link into practice, including social science parks, accelerators tied to social goals, challenge-based methods and social labs of all kinds, before concluding with the core argument: an account of how social science can engage with the emerging field of intelligence design. This is, I hope, a plausible and desirable direction of travel.The rise of data-driven and computational social ScienceWe are all familiar with the extraordinary explosion of new ways to observe social phenomena, which are bound to change how we ask social questions and how we answer them. Each of us leaves a data trail of whom we talk to, what we eat and where we go. It's easier than ever to survey people, to spot patterns, to scrape the web, to pick up data from sensors or to interpret moods from facial expressions. It's easier than ever to gather perceptions and emotions as well as material facts – for example, through sentiment analysis of public debates. And it's easier than ever for organisations to practise social science – whether it's investment organisations analysing market patterns, human resources departments using behavioural science or local authorities using ethnography.These tools are not monopolised by professional social scientists. In cities, for example, offices of data analytics link multiple data sets and governments use data to feed tools using AI – like Predpol or HART – to predict who is most likely to go to hospital or end up in prison.
Keywords: Changement social; Recherche; Réservé UdeM; Université

Nourishing the Social Innovation Debate with the “Social Technology” South American Research Tradition - Pozzebon, Marlei; Tello-Rozas, Sonia; Heck, Isabel (Voluntas, 2021)
Inspired by the South American research tradition known as “social technology,” this article proposes an operational framework to advance the understanding of mechanisms that help to promote social transformation. To illustrate its theorizing potential, we apply the framework to a nonprofit organization–Parole d’excluEs–that was created in Montreal (Canada) in 2006 and that has been promoting citizen mobilization and commitment to social change (parole-dexclues.ca). To that end, we offer a theoretical paper with an empirical illustration as a first step in a reflection on employing a global South theoretical lens–drawing on the concept of social technology–to make sense of a global North social innovation experience and to advance existing knowledge on the mechanisms of social transformation. The results contribute to social innovation research and practice, particularly at the interface between the management and nonprofit literatures.
Keywords: Amérique centrale/sud; Amérique latine; Canada; Changement social; Innovation sociale; Montréal; Nord / Sud; Recherche; Technologie sociale; Transformations

Living Labs, innovation collaborative et écosystèmes : le cas de l’initiative « Concept Maturity Levels » dans les Medtech - Béjean, Mathias; Picard, Robert; Bréda, Gabrièle (Innovations, 2021)
Les Living Labs (LLs) sont de nouvelles formes de laboratoires mettant en œuvre des approches collaboratives et expérimentales centrées sur les utilisateurs. Récemment, les capacités des LLs à développer des réseaux d’innovation ouverts et collaboratifs ont été soulignées. Mais les recherches sont encore peu nombreuses, alors même que le phénomène ne cesse d’évoluer en pratique. En s’appuyant sur l’analyse longitudinale d’une initiative en cours, les « Concept Maturity Levels Santé », impulsée par le Forum des Living Labs en Santé et Autonomie, cet article présente une recherche abductive visant à explorer et caractériser la manière dont les LLs peuvent contribuer, au-delà de projets d’innovation temporaires, à structurer des écosystèmes d’innovation ouverts et collaboratifs sur le long terme. En sus de contribuer à la littérature sur les LLs, l’article ouvre de nouvelles pistes de caractérisation des écosystèmes communautaires d’innovation jusqu’ici encore peu étudiés.Code JEL : M100
Keywords: France; Innovation collaborative; Laboratoire vivant; Recherche; Réservé UdeM; Santé

Expérimenter la recherche-projet en doctorat : applications dans les champs de la santé et du handicap - Fournier, Pierre; Ménard, Manon; Wrembel, Élisa (Etudes de communication, 2021)
Nous proposons un regard réflexif sur deux expériences de recherche-projet menées dans le cadre de thèses de doctorat. Notre réflexion porte sur les apports et limites de cette démarche dans le cadre de projets ancrés dans les champs de la santé et du handicap, plus spécifiquement des troubles du sommeil et des troubles du spectre de l’autisme. La proposition repose sur la démonstration de l’intérêt de la conception participative propre à la recherche-projet dans ces domaines sensibles au sein desquels l’enjeu de l’inclusion des acteurs apparaît comme majeur.
Keywords: Innovation inclusive; Innovation sociale; Projets participatifs; Recherche; Réservé UdeM

Co-creation for Responsible Research and Innovation: Experimenting with Design Methods and Tools - Deserti, Alessandro; Real, Marion; Schmittinger, Felicitas (Springer Series in Design and Innovation, 2022)
This open access book summarizes research being pursued within the SISCODE (Society in Innovation and Science through CO-DEsign) project, funded by the EU under the H2020 programme, the goal of which is to set up an analytical, reflective and learning framework to explore the transformations in initiatives and policies emerging from the interaction between citizens and stakeholders. The book provides a critical analysis of the co-design processes activated in 10 co-creation labs addressing societal challenges across Europe. Each lab as a case study of real-life experimentation is described through its journey, starting from the purpose on the ground of the experimentation and the challenge addressed. Specific attention is then drawn on the role of policies and policy maker engagement. Finally, the experimentation is enquired in terms of its output, transformations triggered within the organization and the overall ecosystem, and its outcomes, opening the reasoning towards the lessons learnt and reflections that the entire co-creation journey brought.
Keywords: Co-création; Idéation, dialogue et maillage; Libre accès; Outils; Recherche; Étude de cas

Sustainability-Oriented Social Innovation Design: The Value of Co-Creation - Yan, Wu; Lei, Ren; Keye, Li (2019 IEEE Eurasia Conference on Biomedical Engineering, Healthcare and Sustainability (ECBIOS), 2019)
From the perspective of sustainability, this paper analyzes how stakeholders realize sustainable social innovation through co-creation. Through literature and case analysis, based on the group classification of social networks, this paper proposes three elements of social innovation: place creation, situation creation and relationship structure, and further sorts out the co-creation of meaning co-creation, behavior co-creation and value co-creation. The research shows that co-creation is a practical activity based on cultural identity, group interaction and resource integration, and stakeholders can achieve the goal of sustainable social innovation through meaning co-creation, behavior co-creation and value co-creation.
Keywords: Co-création; Communautaire; Coopération; Durabilité; Développement durable; Idéation, dialogue et maillage; Innovation sociale; Innovation sociale durable; Nouvelles technologies; Recherche; Réservé UdeM

Unpacking the role of universities in the emergence, development and impact of social innovations – A systematic review of the literature - Bayuo, Blaise Booponoyeng; Chaminade, Cristina; Göransson, Bo (Technological Forecasting and Social Change, 2020)
Widening income and knowledge inequalities have led to growing expectations for universities to integrate social innovation in their core missions as a response to societal problems. This systematic review of literature provides an overview of the state-of-the-art of knowledge on the role of the university in enabling social innovation through its missions of teaching, research and third mission. It also identifies knowledge gaps in the field. A bibliometric approach wasused to identify and analyze books, journal articles and reports examining factors driving social innovation activities at universities, organizational and insitutional change to accommodate such activities as well as their impact. The review reveals that the literature on university engagement in socially-oriented activities as part of the third mission of the university is conceptually well developed and a growing field of inquiry. It also points to gaps in the knowledge base; relatively few studies address issues related to institutional change and incentive structures that influences the ability of universities to engage in social innovation. Likewise, impact studies on social innovation activities at universities are scarce. Further research that builds an impact measurement framework would support the process of integrating social innovation activities in the three missions of the university.
Keywords: Innovation sociale; Mesure d'impact; Recherche; Réservé UdeM; Rôle des universités; Université

A dual-functional social innovation process model for low-cost houses through university-enabled initiative - Belayutham, Sheila; Ibrahim, Che Khairil Izam Che; Zulkifli, Assrul Reedza; Ibrahim, Norhati (Construction Innovation-England, 2019)
The purpose of this study is to develop a dual-functional university-enabled social innovation process model on the subject of low-cost houses that addresses the distinct elements of social obligation and university teaching-learning. Design/methodology/approach This study has predominantly adopted a longitudinal single case study approach, where data have been collected through interviews, survey, participant observation, direct observation and document review. The case study details on the social innovation processes, which was conducted by Universiti Teknologi MARA, Malaysia. Findings This study has demonstrated the social innovation processes toward addressing the issue of insufficient low-cost houses, concurrently benefitting the teaching-learning dimension. Three sub-innovations have been highlighted in the developed social innovation process model, which are collaboration process, teaching-learning and design-construct innovation. Originality/value The development of the social innovation process model for low-cost houses through university-enabled initiative is a novel establishment, particularly for developing nations, as limited studies have been conducted in this regard. The significant insights into how university could play a role in addressing major social issues, along with their core focus (teaching-learning and research development), is a breakthrough for further diffusions of social innovation by universities.
Keywords: Asie; Enseignement; Innovation sociale; Recherche; Rôle des universités; logement

Rediscovering the Cooperative Enterprise: A Systematic Review of Current Topics and Avenues for Future Research - Camargo Benavides, Andres Felipe; Ehrenhard, Michel (VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations, 2021)
For decades, the cooperative enterprise (CE) produces market goods and/or provides services in the interest to its members, such as communities, customers, and suppliers. The upsurge of interest in social enterprises, and their balancing of social and economic interests, has also led to a renewed interest in CEs, often seen as a speciﬁc type of social enterprise. However, from an organizational perspective, this renewed interest has been both limited and scattered over a variety of ﬁelds. In this paper, we systematically review papers on CE in the mainstream organizational literature, deﬁned as literature in the ﬁelds of economics, business, management and sociology. Our review integrates and synthesizes the current topics in the mainstream organizational literature and provides a number of avenues for future research. In addition, we compare our ﬁndings in the organizational literature to the social issues literature as these appeared to be quite complimentary. We found multilevel studies, determination of social impact—in particular measurable impact, managerial practices for sustainable (organisational) development, and the entrepreneurial opportunity generation process as the four key avenues for future research.
Keywords: Coopératives; Entreprise; Entreprise sociale; Recherche; Réservé UdeM